Counter-Reformation Theology and Art: The Example of Rubens's Paintings of the Passion - Viladesau, Richard (Toronto journal of theology, 2012)
The Counter-Reformation period is a rare example of a direct influence of theological ideas on painting—not only in themes but also in style. The altarpieces of Peter Paul Rubens are a supreme example of baroque Catholic painting that translates Tridentine theology into art.